Swell and compressibility of fly ash−clay blends in lumps and powders: effect of 4% lime. Issue 1 (20th February 2022) - Phanikumar, B. R.; Nagaraju, T. V.; Mounika, K. N.
Abstract : This paper describes the influence of fly ash on the swell-compressibility characteristics of an expansive clay passing through a 4·75 mm sieve. The free-swell index (FSI), heave, swell potential, swelling pressure, coefficient of compressibility ( a v ), the compression index ( C c ) and linear shrinkage (LS) of fly ash–clay blends were studied. Fly ash content was varied from 0, 5, 10, 15 to 20%. Swelling and compressibility of the clay decreased with increasing fly ash content. Heave was the lowest at 15% fly ash. The paper compares the effect of 15% fly ash on the swell-compressibility behaviour of clay lumps passing a 4·75 mm sieve and clay powder passing a 425 μm sieve. While the swell potential was found to be higher for clay powder than for clay lumps at 15% fly ash, the swelling pressure was higher for clay lumps. As 4% lime resulted in the highest reduction of the FSI, a series of swell-consolidation tests and a series of FSI tests were conducted on fly ash–clay blends to which 4% lime was added. FSI, heave and swelling pressure decreased on the addition of fly ash. They further decreased when 4% lime was added. The parameters a v, C c and LS also reflected a similar trend.